Differential expression involved in starch synthesis pathway genes reveal various starch characteristics of seed and rhizome in lotus (Nelumbo Nucifera). Issue 9 (20th August 2022) - Zhu, Fenglin; Sun, Han; Wang, Jia; Zheng, Xingwen; Wang, Tao; Diao, Ying; Hu, Zhongli
Abstract : Abstract: Lotus ( Nelumbo nucifera ) is one of the main aquatic vegetables in China. Its seed and rhizome are main edible parts which are rich in starch. Preliminary experiments of starch contents revealed that seed and rhizome expressed great differences in amylose and amylopectin contents. The rhizomes have higher amylopectin content, while the seeds have higher amylose content. In this study, we have estimated 16 varieties of lotus seeds and found that the amylose content of lotus seeds ranged from 30% to 50%, with an average amylose content of 43%, which showed high‐amylose content characteristics. Morphological analysis of lotus seed shown that starch rapid accumulated in 20 DAF (day after fertilization) ∼ 26 DAF. Transcriptome of lotus seeds indicated that starch genes played an important role in seed development. Especially in 22 DAF, the genes which controlled amylose synthesis significantly increased, in contrast, the expression of amylopectin‐related genes was stable and might limit the synthesis of amylopectin. We further analyzed the expression patterns of 11 key related genes between lotus seeds and rhizomes, and found that the expression of amylose‐related genes to were higher in lotus seed, while the expression of genes related to amylopectin synthesis were higher in rhizome. This study provided a comprehensive research of molecular basis for starch in lotus seed and rhizome. Different expression among key genes during starch accumulation might be the principal cause of the differences in starch properties between seed and rhizome. Practical Application: Differential expression involved in starch synthesis pathway genes is the main reason for various starch characteristics of seed and rhizome in lotus. High amylose content in lotus seed is a valuable trait for developing functional food.